INTRINSIC REGISTRATION TECHNIQUES FOR MEDICAL IMAGES: A STATE-OF-THE-ART REVIEW - Alam, Fakhre; Rahman, Sami Ur (Journal of Postgraduate Medical Institute, 2016)
Medical image registration is the process of mapping two or more medical images into a single more informative image for the purpose of receiving precise and complementary information. The precise mapping of medical images obtained in different time- frames and by the same or different modalities is now possible due to the availability of large number of registration techniques. The purpose of this paper is to present and analyse intrinsic registration techniques for medical imaging in a comprehensive manner. Our approach of analysis is unique from already published work because we have performed detailed investigation on each registration techniques, and analyse similarity measures and assessments according to various parameters. The knowledge on the work that has been developed in the area is presented in a compact form. This work is expected to provide a useful platform for the researchers in the field of medical image registration in general and in intrinsic registration in particular.